The Effect of Hosting Mega-Sporting Events on Asian Countries’ Economic Growth - Rifqi Muhammad Aufa; Akhmad Syakir Kurnia (Diponegoro Journal of Economics, 2025)
This study aims to see the effect of hosting mega-sporting events: the FIFA World Cup, Summer Olympics, and Winter Olympics on Asian countries’ economic growth, such as China, Indonesia, Japan, South Korea, Thailand, Bahrain, Singapore, Saudi Arabia, Malaysia, and India from 1998 to 2023. This study compares the effects of each Mega-Sporting Event (MSE) across nations using panel data.  Because it takes into consideration country-specific factors that could affect the outcomes, the Fixed Effect Model (FEM) was used.  Hosting the FIFA World Cup did not have a positive effect on economic growth, hosting the Summer Olympics brought a positive effect on economic growth, and hosting the Winter Olympics did not have a positive effect on economic growth. A limitation of this study is that it did not include Qatar because the variables used in the research were unavailable. Additionally, the study did not examine the indirect effects of hosting mega-sporting events on economic growth. This study offers a novel cross-country panel analysis on the economic impact of hosting MSEs in Asia over 26 years using a Fixed Effect Model.